Refuse-derived fuel policy frameworks and stakeholder engagement: Case study in Padang City, Indonesia - Alsafana Rasman; Evi Frimawaty; P. Arief Budiman (Indonesian Journal of Social and Environmental Issues (IJSEI), 2026)
Indonesia faces significant challenges in waste management, with most waste ending up in landfills, contributing to environmental pollution and greenhouse gas emissions. To address landfill overcapacity, Padang City initiated Refuse-Derived Fuel (RDF) processing at Aie Dingin Landfill, supported by the cement industry as an off-taker. However, policy frameworks for Waste to Energy (WtE) remain limited in Indonesia, posing governance challenges. This research investigates governance readiness for sustainable RDF implementation in Padang City, focusing on policy frameworks and stakeholder engagement. Employing a mixed-methods approach involving content analysis of regulations and stakeholder interviews, the study finds that both national and sub-national policy frameworks provide a robust legal foundation for RDF. Padang City demonstrates strong local commitment through its Waste Management Master Plan (2024–2044), which designates RDF development as a priority. Nevertheless, significant governance gaps persist at the national level due to the lack of comprehensive technical standards for WtE technologies. Additionally, waste management is categorized as a “non-basic service compulsory affair” under Law No. 23 of 2014, potentially leading to lower prioritization in local planning. The stakeholder analysis reveals that while formal roles are outlined by law, practical implementation involves expanded responsibilities. Non-regulated actors like academia and informal waste workers are not yet formally integrated into legal instruments, despite vital contributions through research, pre-sorting, and waste segregation. The paper concludes that addressing these governance gaps through adaptive policy instruments and inclusive institutional arrangements is essential for long-term RDF implementation success.